SUBKULTUR NARAPIDANA DI LEMBAGA PEMASYARAKATAN - Titik Suharti (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2002)
Penitentiary is a place for a convicted criminal or a prisoner to spend their condemnation period. The main purpose of penitentiary or correctional facility is as re-socialization of a prisoner, so that after the condemnation period is over, she or he will be able to come back to the community in a better behaviour. During the period in the penitentiary, a prisoner will experience some kind of deprivation that leads into prisoner subculture.